Growth performances , carcasses parameters and meat fatty acid composition of lamb fed green oak acorns ( Quercus ilex ) based diet - Keddam, Ramdane; Bouderoua, Kaddour; El-affifi, Mohamed; Attou, Ghalem Selselet- (African Journal of Biotechnology, 2010)
The aim of this experiment is to compare the effects of diets containing green oak acorns (GO) and barley (BL) on the growth performances, carcasses parameters and the composition in fatty acids of lambs. Two groups of five lambs each were fed, respectively, during 105 days with diets containing 50% of oaks acorns and 50% of barley. At the end of the test, the animals of the two diets expressed comparable body weights and weight gain. A significant difference (P < 0.05) was observed for the thickness of fat cover which is 3 mm for the BL group against 1.6 mm for GO group even if no significant difference was revealed concerning the output with slaughtering. The intramuscular lipids were significantly higher (P < 0.05) in the group of animals fed with GO diet compared to the BL diet (3.88 vs 2.83 g.100-1 g of muscle). Among the saturated fatty acids (SFA), the stearic acid significantly appeared in higher proportion (P < 0.05) in GO diet (20.8 vs 18.1%) whereas the palmitic acid is prevalent in the group of animals fed with the BL diet (25 vs 30%). For the polyunsaturated fatty acid (PUFA), no significant difference was observed between the two groups. The linoleic acid is prevalent among the PUFA of two groups without significant difference. The linolenic acid is higher in the animal fed BL. The n-6: n-3 ratio is higher in the BL group (8.9 vs 7.3). At the end, the low level of incorporation of PUFA in muscle of the lamb because of biohydrogenation, suggests us supplementing the diet by green grass.
Keywords: barley; fatty acid; lamb; meat; oak acorn

Fatty acid composition of abdominal adipose tissue in broilers fed green-oak (Quercus ilex), cork oak acorn (Quercus Suber L.) based diets - Bouderoua, Kaddour; Selselet-Attou, Ghalem (Anim. Res., 2003)
Male broilers, 30 for every diet, were fed for six weeks, diets containing 60% green oak (GO) and oak cork (CO) acorns compared to 60% corn (C). The body weight of the chickens fed the oak acorn-based diets was 25% lower than that of the controls (C). Abdominal adipose tissue (AAT) was twice heavier in the controls compared to broilers fed oak acorn-based diets. The total lipids of AAT were higher in the controls compared to the oak acorn fed chickens (34.4 against 15.3 g per 100 g of AAT in the CO). The palmitic and oleic acid proportions were comparable in the AAT of chickens fed with the different diets. The proportion of linoleic acid, obtained exclusively by the diets, was significantly higher in the chickens fed oak acorn-based diets (23%), compared to the controls (19%). Reciprocally, palmitoleic acid was present in a small proportion in chickens fed oak acorns (4 to 5%). The observed variation of the fatty acid content of abdominal fat of acorn-fed chickens requires further research on the precise nutrient digestibility of oak acorns before considering them as a potential feed.
Keywords: Adipose Tissue; broilers; Lipids; lipogenesis; oak acorn

Fatty acid composition of abdominal adipose tissue in broilers fed green-oak (Quercus ilex), cork oak acorn (Quercus Suber L.) based diets - Bouderoua, Kaddour; Selselet-Attou, Ghalem (Anim. Res., 2003)
Male broilers, 30 for every diet, were fed for six weeks, diets containing 60% green oak (GO) and oak cork (CO) acorns compared to 60% corn (C). The body weight of the chickens fed the oak acorn-based diets was 25% lower than that of the controls (C). Abdominal adipose tissue (AAT) was twice heavier in the controls compared to broilers fed oak acorn-based diets. The total lipids of AAT were higher in the controls compared to the oak acorn fed chickens (34.4 against 15.3 g per 100 g of AAT in the CO). The palmitic and oleic acid proportions were comparable in the AAT of chickens fed with the different diets. The proportion of linoleic acid, obtained exclusively by the diets, was significantly higher in the chickens fed oak acorn-based diets (23%), compared to the controls (19%). Reciprocally, palmitoleic acid was present in a small proportion in chickens fed oak acorns (4 to 5%). The observed variation of the fatty acid content of abdominal fat of acorn-fed chickens requires further research on the precise nutrient digestibility of oak acorns before considering them as a potential feed.
Keywords: Adipose Tissue; broilers; Lipids; lipogenesis; oak acorn